GAYA KEPEMIMPINAN WALI NAGARI SIMARASOK KECAMATAN BASO KABUPATEN AGAM SEBAGAI NAGARI TERBAIK TINGKAT NASIONAL TAHUN 2011 - Azward Hanafiah P; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Success or failure of an organization partly determined by the quality of its leaders who have senteral function in their duties especially in the area of leadership that has customs that are still thick. Leadership in the philosophy of traditional customs have tigo sajarangan Furnace (Tali Tigo Sapilin) that must be adhered to by every leader in kenagarian, not all leaders can menjalannkannya. Muslim father Datuk Payung Diaceh received recognition from the community and demonstrated with the award for best national villages in 2011. This study used a qualitative method that seeks to provide an overview of the status of the case, known as descriptive research. Descriptive research is research that systematically illustrates the facts or characteristics of a particular population factually and accurately. This research was conducted at the Office of the Nagari Simarsok Agam District of Baso In this study the authors informant Simarasok Mr. Wali Nagari Muslim Muslim Datuk Payung diaceh, Secretary Nagari, Cedik Clever, ninik mamak, Density Traditional Nagari, Head Jorong, and Peoples.The results showed that Mr. Muslim Dutuk Payung Diaceh is a leader who has the charisma in everyday life and in government is a role model in kenagarian he also has a leadership style that encourages participatory mansyarakatnya proven to advance in the construction of the village awarded best national in 2011 supporting factors such as nagari Simarasok Natural Resources (NR), Human Resources (HR) and staff-staff experts mempuni, big society participation in governance and the race village, the support of indigenous stakeholders whoalways gives good motivation to the village trustees and the community and supported by the local government in collaboration with private individual or by PLN and its Andalas University.Keywords: Leadership Style, Wali Nagari, Muslim Datuk Umbrella diaceh, 2011 National Best Village